Constitutional reform: theoretical issues - Udartsev, S.F. (Právo a bezpečnost, 2016)
At the same time it shall be remembered that even if the text of the constitution has been changed fully its role and meaning are not exhausted and implemented. The development of the constitution is not limited only by changing its text but it includes its interpretation, the improvement of the legislation based on it, development of institutions on human rights, legal education, legal professional and public consciousness, legal culture as well. In order to improve and implement the provisions of the constitution it is necessary to involve all means providing the disclosure of its positive potential. At the same time it is necessary to follow the events, impartially analyze the appeared problems and take measures in proper time aimed at correlating the implementation of the constitution and the correspondence of its text to the condition of the society, challenges of time, and correspondence to the legal policy.
Keywords: constitutionalization; constitutional reform; legitimacy; Research Subject Categories::LAW/JURISPRUDENCE